A New Route to Roflumilast via Copper-Catalyzed Hydroxylation - Ni, Feng; Li, Jianqi (Synthesis, 2012)
A new route to Roflumilast, a selective phosphodiesterase type 4 (PDE 4) inhibitor, is described. The synthetic procedure starts from 4-hydroxy-3-iodobenzoic acid to access the key intermediate 3-(cyclopropylmethoxy)-4-(difluoromethoxy)benzoic acid via copper-catalyzed hydroxylation and utilizes amide coupling to accomplish the synthesis of Roflumilast in 80% overall yield.
Keywords: Roflumiast; PDE4 inhibitor; preparation; hydroxylation; copper catalyzed